Observaciones metodológicas sobre el estudio de lenguas extintas en el nororiente peruano: el caso del chacha - Ziemendorff, Michaela (2023)
This article discusses three recent publications on the linguistic classification of Chacha, a language attributed to the ethnic groups of the “Chachapoyas” region in the southern part of the department of Amazonas, Peru. It examines the comparison between Chacha and the languages of the Cahuapanan family undertaken by Rojas-Berscia (2020), as well as the comparative studies conducted by Jolkesky (2016) and Urban (2020), both of which classify Chacha as a Cholonoid language. The analysis focuses on the methodologies applied by the authors, discussing the potential and limitations of lexical and phonetic comparisons between the languages involved, the methods and constraints of toponymic research, the critical use of historical sources, as well as the method of triangulation. Also, the available sources for a potential comparative analysis of the Chacha language and neighboring languages are discussed and evaluated, coming to the conclusion that, for the moment, the scarcity of the material does not allow any classification of the Chacha language. Finally, the article defines the most suitable methodological approaches for the investigation of Chacha and other extinct and undocumented languages of the region in general, proposing, among others, an expansion of the toponymic and anthroponymic database before historical linguists might proceed with any kind of analysis.